Effect of aquatic training program on pain and posture among obese females with bilateral knee osteoarthritis - Sandeep Shinde; Pooja Jain (Journal of Kinesiology and Exercise Sciences)
Background: Knee osteoarthritis (KOA) is the most common type of arthritis, causing pain, stiffness, muscular weakness, and difficulty walking, all of which discourage activity and contribute to the growing obesity pandemic as a public health concern. KOA has a considerable effect on the alignment of the spine-pelvis-lower extremity axis. Joint alignment is the main patho-physiological factor that contributes to the progression of KOA. There is little literature addressing biomechanical aspects that affect osteoarthritis and its progression, such as malalignment. The aim of this research was to investigate and compare the effects of land-based exercise (LBE) and aquatic exercise (AQE) on pain and posture in obese females with bilateral KOA. Methods: This randomized controlled trial involved 157 obese women with bilateral KOA, of whom 7 refused to participate for various reasons. Ultimately, 150 females participated and were assigned to two different groups, Group A and Group B. They received aquatic exercise (AQE) and land-based exercise (LBE) for eight weeks. Results were evaluated using VAS, Postural Evaluation, Active Knee Extension Test (AKE), Modified Thomas Test, MMT, WOMAC, and SF-36 with statistical analysis using SPSS software. Results: The results demonstrated a statistically significant benefit of the aquatic exercise program compared to the landbased exercise program for obese females with bilateral KOA. Pain was significantly reduced (p<0.0001), whereas, posture, MMT, hip and knee flexibility, WOMAC, and quality of life were all improved (p<0.0001). Conclusion: The effect of aquatic exercise on pain and posture among obese females with bilateral KOA was found to be significant for reducing pain and improving posture, range of motion, muscle strength, and quality of life.